Bactericidal activity of a substituted thiazole against multidrug-resistant Eggerthia catenaformis isolated from patients with dental abscess. (June 2021) - Ibrahim, Yasser Musa; Nasr, Tamer; Bondock, Samir; Assar, Nouran H.
Abstract: Human infections caused by the anaerobic bacterium Eggerthia catenaformis are rare. However, a growing number of case reports have presented the bacterium as the causative agent in many serious complications. This study provides data on the isolation and antibiotic susceptibility profiles of E. catenaformis from dental abscess. Identification of isolates was performed using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). We also investigated the antibacterial activity of 5-acetyl-4-methyl-2-(3-pyridyl) thiazole (AMPT) on E. catenaformis isolates. Minimum inhibitory concentrations (MICs) were determined by an agar dilution method and bactericidal activity was evaluated by a time-kill assay. Moreover, the mechanism of action of AMPT was also explored by cell membrane disruption assay and scanning electron microscopy (SEM). MALDI-TOF MS results revealed unambiguous identification of all isolates with score values between 2.120 and 2.501. Isolates NY4 and NY9 (20% of isolates) were found resistant to multiple antibiotics judged by MIC values. As multidrug-resistant strains of E. catenaformis were not reported to date, we then confirmed the identity of NY4 and NY9 based on 16S rRNA gene sequence. Favorably, all isolates were susceptible to AMPT with an MIC range of 0.25–1 mg/L. Time-kill kinetics of AMPT indicated that it exhibited potent bactericidal activity against the multidrug-resistant isolates NY4 and NY9. Furthermore, this study also hypothesizes that AMPT exerts its antibacterial effect through damaging the cell membrane and thereby induce the release of intracellular components. AMPT could therefore be considered as a therapeutic option for infections caused by multidrug-resistant bacteria. Graphical abstract: Image 1 Highlights: First report on the emergence of multidrug-resistant Eggerthia catenaformis . Antibiotic susceptibility of E. catenaformis from dental abscess is provided. A thiazole (AMPT) is bactericidal against multidrug-resistant E. catenaformis . AMPT induced lysis of E. catenaformis cells by targeting cell membrane. Cell lysis was confirmed by scanning electron microscopy.